Seasonal variation of human semen parameters: A retrospective study in Italy. (June 2015) - De Giorgi, A.; Volpi, R.; Tiseo, R.; Pala, M.; Manfredini, R.; Fabbian, F.
<x xml:space="preserve">Abstract</x> Introduction: Human infertility is a common condition secondary to many primary or secondary causes. As for these latter, different seasonal and climatic patterns have been hypothesized to play a role. The aim of this study was to assess the presence of a possible seasonal pattern in the functional parameters of semen samples maintained in a large tertiary center database. Materials and methods: The reports of spermograms of 5188 consecutive subjects, collected at the Center for Reproductive Incapacity of the University Hospital of Parma during a 11-year period (2003–2014), were retrospectively analyzed. The reports included sperm motility, volume, and number, as well as pH, swelling and eosin tests. Data of different parameters were analyzed by season of sample collection. The ANOVA test was used for the evaluation of continuous variables, after Log transformation in case of a non-normal distribution, while χ2 test was used for categorical variables. Moreover, logistic regression analysis was performed, to identify factors independently associated with normal sperm motility. Results: Compared with the other seasons of the year, a higher sperm motility was found during the summer. Moreover, the prevalence of samples with a normal sperm pH (7.2–8) was higher during the spring, whilst the volume of sperm was higher in winter. Logistic regression analysis showed that normal sperm motility (>40%) was independently associated with spring (1.227; 95% CI 1.077–1.507, p = 0.005), summer (2.031; 95% CI 1.689–2.442, p < 0.001), swelling test (1.953; 95% CI 1.670–2.284, p < 0.001), eosin test (2.804; 95% CI 2.477–3.174, p < 0.001), pH (0.507; 95% CI 0.346–0.743, p < 0.001), LOG-number (2.949; 95% CI 2.470–3.522, p < 0.001) and LOG-volume (2.216; 95% CI 1.696–2.894, p < 0.001) of semen. Conclusion: This study suggests the existence of a positive relationship between some semen parameters and seasons.